2015
DOI: 10.5389/ksae.2015.57.1.069
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Irrigation Return Flow in a Reservoir Irrigated District

Abstract: The objective of this study was to investigate characteristics of irrigation return flow from paddy block in a reservoir irrigated district during growing seasons. The irrigation return flow was divided into three parts, quick return flow from irrigation canal (RFI), quick return flow from drainage canal (RFD), and delayed return flow (DRF). The RFI was calculated from water level and stage-discharge relationships at the ends of the irrigation canals. The DRF was estimated using measured infiltration amount fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…At the paddy block scale, the components of surface water draining out of the main outlet can be expressed as: (4) where is total surface drainage in a paddy block (mm); is paddy field drainage (mm) that is excess water discharged from paddy fields and collected in the drainage ditch ( Figure 1); and is the time step (day). In a modeling approach, can be simulated as a fraction of [5,6,8,15]: ( 5) where is the delivery management coefficient (fraction); and represents a year. It has been reported that varies depending on farming practices and weather conditions [5,8,15].…”
Section: Paddy Drainage Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…At the paddy block scale, the components of surface water draining out of the main outlet can be expressed as: (4) where is total surface drainage in a paddy block (mm); is paddy field drainage (mm) that is excess water discharged from paddy fields and collected in the drainage ditch ( Figure 1); and is the time step (day). In a modeling approach, can be simulated as a fraction of [5,6,8,15]: ( 5) where is the delivery management coefficient (fraction); and represents a year. It has been reported that varies depending on farming practices and weather conditions [5,8,15].…”
Section: Paddy Drainage Modelmentioning
confidence: 99%
“…Irrigation water supplied from sources such as reservoirs, pumping stations, and tube wells may not be consumed in plots and rather may directly discharge into drainage canals and downstream streams. Such water is known as irrigation return flow (RF), affecting the flow regime of the downstream rivers [1][2][3][4][5][6]. RF is an important part of the water balance of a watershed and a critical factor requiring consideration when developing water resources management plans and practices, determining the operation rule of irrigation systems, and assessing environmental water use [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…서 론 농업용수 공급량(agricultural water supply)은 관리자 가 수리시설물에서 관개지구로 실제로 공급하는 용수량을 의미하며 농경지에서 작물재배를 위해 이용되는 필요수량 (irrigation water requirement), 수로에서 손실되는 송수 손실 수량(conveyance loss), 그리고 포장으로 유입되지 않고 하천으로 직접 회귀하는 배분관리 용수량(delivery management water requirement)을 포함한다 Song et al, 2015).…”
unclassified
“…농업용 저수지는 관개 후 수위가 내려가고, 상류유 역의 유출량이 유입되어 다시 수위가 상승한다. 저수지 하류 관개지구로 공급된 용수량은 전량 작물에 의해 소비 되는 것이 아니며, 약 32∼86%가 포장에서 소비되지 않고 하천으로 회귀되어 하천유량을 구성하는 중요 성분이 된 다 (Song et al, 2015). 이와 같이 농업용수 공급은 관개지 구의 수문 순환과 비관개지구의 수문 순환, 그리고 수리 시설물의 저수량 등과 복합적으로 연계되어 상·하류의 하 천 유황에 영향을 미친다.…”
unclassified